Fast arc retreat in the eastern Mediterranean: constraints from late Campanian forearc deposits (Donousa, Greece) - S. O. Martha; P. Xypolias; C. Cheng; W. Dörr; A. Gerdes; D. C. Hezel; M. Kutzschbach; L. Millonig; H. Schmeling; H. R. Marschall; W. Müller; G. Zulauf (International Journal of Earth Sciences, 2025)
The island of Donousa consists of a variegated metasedimentary sequence cut by arc-type granitoid dykes. Detrital zircon U–Pb ages and the presence of volcanic and ultramafic detritus suggest that the protoliths of the metasedimentary rocks were deposited in a Campanian forearc basin later than 76 Ma. D1 stacking of the forearc deposits occurred at upper crustal levels (P max = 0.4 GPa) with staurolite present as a stable phase. The subsequent isobaric heating led to growth of andalusite followed by D2 extension in the stability field of sillimanite, K-feldspar and high-quartz ( P = 0.3 GPa, T = 660 °C). Based on U–Pb ages of garnet (74.6 + 2.3/ − 2.5 Ma) and zircon (74.0 ± 0.8 Ma), separated from an early monzogranite dyke, the timing of forearc deposition, Buchan metamorphism, D2 extension and dyke emplacement is constrained to a maximum period of 2.6 m.y. in the late Campanian. Cooling below T = ca. 600 °C occurred during the Maastrichtian (71.3 + 0.6/ − 1.3 Ma, U–Pb on titanite) and was followed by D3 folding under greenschist facies conditions. A younger generation of Danian granitoid dykes (64.1 + 0.9/ − 1.4 Ma, U–Pb on titanite; 60 ± 4 Ma, Rb–Sr on muscovite) intruded at higher structural levels and was associated with a pervasive fluid-assisted overprint. The sequence of forearc deposition, burying, Buchan metamorphism, extension, and igneous dyking within < 2.6 m.y. is strong evidence for fast (ca. 4 cm a −1 ) trenchward arc retreat that was probably related to late Campanian subduction accretion and magmatic flare-up. Graphical abstract